Perilaku Berisiko dan Keluhan Subjektif Memori (KSM) pada Kelompok Umur 25 Tahun ke Atas di Kota Bogor Tengah - Julianty Pradono (Media Penelitian dan Pengembangan Kesehatan, 2018)
The prevalence of subjective cognitive complaints (SCC) is increasing over the last 10 years. Subjectivecognitive complaints reflect early signs of neurodegenerative disease that will develop into dementia. Theobjective of the study was to obtain the incidence rate of SCC and to get predictors of SCC in Bogor City.The sample was prospective cohort sample as much as 3260 respondents with mean age 47.6 ± 9.7 yearsand no SCC at the beginning of analysis. Data were collected by interview, measurement and laboratoryexamination every 2 years. The risk factors include characteristics, health status and risk behavior. Datawas analyzed using chi-square test and regression logistic. The incidence of SCC was 216 persons per1,000 population per 2 years. After adjusting for age, the SCC predictors were less physical activity (OR1.9 time; 95% CI: 1.6-2.3), central obesity (OR 1.2; 95% CI: 1.0-1, 5), intake of sodium ≥2000 mg per day(OR 0.6; 95% CI: 0,5-0,7), mental disorder (OR 1.9; 95% CI: 1.6-2.3 ) and migraine (OR 1.6 times, 95% CI:1.3-1.9) on the incidence of SCC. It is concluded that the incidence rate of SCC is 216 people per 1,000population per 2 years. Predictors of SCC are less physical activity, central obesity, intake of sodium ≥2000mg per day, mental disorders and migraine. It is suggested that specific interventions such as increasingphysical activity regularly, maintaining ideal body weight with no risk of abdominal obese, avoiding stressand controlling salt intake, especially in elderly respondents do not take too low intake. Abstrak Prevalensi keluhan subjektif memori (KSM) semakin meningkat.Keluhan subjektif memorimencerminkan tanda awal penyakit neurodegeneratif yang akan berkembang menjadi demensia. Tujuan penelitian ini untuk mendapatkan incidence rateKSM dan mendapatkan prediktor terjadinya KSM di Kota Bogor.Sampel penelitian merupakan subsampelkohor prospektif sebanyak 3260 responden dengan rerata umur 47,6±9,7 tahun dan bebas KSMdi awal analisis.Data dikumpulkan dengan metode wawancara, pengukuran, dan pemeriksaan yang dilakukan setiap 2 tahun.Faktor risiko meliputi karakteristik, status kesehatan dan perilaku berisiko.Analisis data dengan uji chi-square dan logistik regresi.Hasilpenelitian menyatakan insiden KSMsebesar 216 orang per 1.000 penduduk per 2 tahun.Setelah menyesuaikan faktor umur, prediktor KSM adalah kurang aktivitas fisik (OR 1,9 kali, 95% CI:1,6-2,3), obesitas sentral (OR 1,2 kali, 95% CI:1,0-1,5), asupan natrium ≥2000 mg per hari (OR 0,6 kali, 95% CI: 0,5-0,7), gangguan mental (OR 1,9 kali, 95% CI:1,6-2,3) dan migren(OR 1,6 kali, 95% CI:1,3-1,9) terhadap insidens KSM. Disimpulkan bahwa insiden KSM sebesar 216 orang per 1.000 penduduk per 2 tahun. Prediktor KSMadalah kurang aktivitas fisik, obesitas sentral, asupan natrium ≥2000 mg per hari, gangguan mental dan migren.Disarankan bahwa intervensi spesifik perlu dilakukan pada prediktor KSM.